Idealist, Realist or Neo-Realist Financial Aid Donors to Pakistan - Lubaina Dawood; Khadija Karim; Gul Nagina; Niamatullah (Technium Social Sciences Journal, 2020)
Foreign aid has always been an important source of finance for Pakistan. The flow of foreign aid depends upon the donor’s interest and motives that can differ as some may be truly interested in helping the recipient nation (Mumtaz, 2013). Some donors may have a national interest while others may want to enhance their economic relations which refer to the idealist, realist, and neo-realist theories of motivations respectively (Berthelemy, 2005). The present inquiry is informed by a qualitative interpretive approach based on semi-structured interviews regarding financial aid donor’s motives. The overall results revealed people’s perception that America has an inclination for both Pakistan’s nation and region for its own benefits whereas the United Kingdom is interested in human resources. Saudi Arab and China have dual motives, one is the development of Pakistan and the other is security and trade interest respectively. So America is proclaimed as realist donors, United Kingdom as Neo-realist while Saudi Arab and China have mixed motivations. Both are Idealists with some realist and neo-realist motivation correspondingly. However other financial aid donors are not prominent amongst the Pakistani nations.